Evaluation of Resistance to Malathion and Pirimiphos Methyl in Strains of Tribolium castaneum (Herbst) collected in Indonesia. - Osman, Noorma; Rejesus, B. Morallo (1981)
Fifty-six strains of Tribolium castaneum (Herbst) collected from BULOG and commercial godowns of village co-operative units and farmers' padi storage units from many parts of Indonesia were tested for resistance to malathion and pirimiphos methyl. Forty-nine of these strains showed various degrees of resistance while seven showed a susceptible response to malathion. All the strains of T. castaneum were susceptible to pirimiphos methyl. The dominant species of Tribolium spp. in Indonesia was found to be T. castaneum (Herbst).